2022
DOI: 10.1007/s12144-022-03553-6
|View full text |Cite
|
Sign up to set email alerts
|

Never mind losing the pound… still got the penny! The influence of trait greed on risky decision behavior in a mixed and gain only BART

Abstract: Risk proneness and the lack of loss aversion are two different reasons to show varying degrees of risk-taking in decision situations. So far, little is known about the extent to which these two processes underly the influence of trait greed, trait anxiety, and age. The present study investigated risk- taking in decision making in these trait contexts using two variants of the Balloon Analogue Risk Task (BART) in an online study: A gain only and a mixed gambling BART. This was done to separate risk proneness fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Li et al (2019) found that the DGS negatively correlated with loss aversion but not with risk attitude. Rodrigues et al (2022) found that individuals with high greed showed increased risk decisionmaking in the Balloon Analogue Risk Task (BART; Lejuez et al, 2002 ). In the finance domain, Hoyer et al (2021) tested the effects of the motive of greed on individual trading behavior in experimental assets markets and found that participants' level of greed did not influence trading activity.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2019) found that the DGS negatively correlated with loss aversion but not with risk attitude. Rodrigues et al (2022) found that individuals with high greed showed increased risk decisionmaking in the Balloon Analogue Risk Task (BART; Lejuez et al, 2002 ). In the finance domain, Hoyer et al (2021) tested the effects of the motive of greed on individual trading behavior in experimental assets markets and found that participants' level of greed did not influence trading activity.…”
Section: Introductionmentioning
confidence: 99%